Effective Academic Writing 3. The Essay - Davis J. Jason (New York, Oxford University Press, 2006)
The Effective Academic Writing series teaches the writing modes, rhetorical devices and language points required for academic success. Each of the three levels provides user-friendly activities and self-contained lessons that make teaching and learning manageable. Each unit introduces a theme and a writing task and then guides the student writer through the process of gathering ideas, organizing an outline, drafting, revising and editing. Students are given the opportunity to explore their opinions, discuss their ideas, and share their experiences through written communication. Effective Academic Writing 3: The Essay introduces students at the high intermediate to low advanced level to five-paragraph essays, while introducing five essential rhetorical modes. Features: Compelling and authentic readings inspire student interest before writing modes are introduced. Rhetorical presentations and exercises refine writing skills. Language presentations and exercises complement writing genres. Editing checklists promote peer feedback and aid students in revising their written work. Timed essay writing and testing material at the end of each unit reinforce skills and prepare students for in-class writing as well as high-stakes assessment. Grammar presentations and practice are correlated to Grammar Sense 3.